2014
DOI: 10.1007/s12185-014-1528-8
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the dose of aclarubicin in low-dose cytarabine and aclarubicin in combination with granulocyte colony-stimulating factor (CAG regimen) can safely and effectively treat relapsed or refractory acute myeloid leukemia

Abstract: It is difficult for relapsed and refractory acute myeloid leukemia (AML) patients to achieve complete remission (CR). The CAG regimen [low-dose cytarabine and aclarubicin in combination with granulocyte colony-stimulating factor (G-CSF)] has been used to treat relapsed and refractory AML patients, and showed good therapeutic efficacy. It is unknown, however, whether increasing the dose of aclarubicin in CAG regimen could treat relapsed or refractory AML safely and effectively. We evaluate the efficacy and tole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 22 publications
1
12
0
2
Order By: Relevance
“…The HD-CAG regimen consisted of Ara-C 10 mg/m 2 injected subcutaneously every 12 h from day 1 to day 14, aclarubicin 5-7 mg/m 2 [age ≥ 65 years or had poor performance status (ECOG performance status 3) were treated with aclarubicin 5 mg/m 2 ] infused intravenously daily from day 1 to day 14, and G-CSF administered subcutaneously at a dose of 200 g/m 2 /day, unless patient WBC count was ≥20 × 10 9 /L [20]. G-CSF subcutaneously was first administered immediately before the first injection of Ara-C, and was stopped 12 h before the last injection of Ara-C. At the time of treatment, if WBC count was ≥20 × 10 9 /L, the administration of G-CSF was postponed.…”
Section: Treatment Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…The HD-CAG regimen consisted of Ara-C 10 mg/m 2 injected subcutaneously every 12 h from day 1 to day 14, aclarubicin 5-7 mg/m 2 [age ≥ 65 years or had poor performance status (ECOG performance status 3) were treated with aclarubicin 5 mg/m 2 ] infused intravenously daily from day 1 to day 14, and G-CSF administered subcutaneously at a dose of 200 g/m 2 /day, unless patient WBC count was ≥20 × 10 9 /L [20]. G-CSF subcutaneously was first administered immediately before the first injection of Ara-C, and was stopped 12 h before the last injection of Ara-C. At the time of treatment, if WBC count was ≥20 × 10 9 /L, the administration of G-CSF was postponed.…”
Section: Treatment Protocolmentioning
confidence: 99%
“…In previous studies, we found that the CAG regimen [aclarubicin (ACR), cytarabine (Ara-C) and granulocyte colony-stimulating factor (G-CSF)] showed significant treatment potential for relapsed or refractory ALL, especially for T-ALL patients [18,19]. We have reported that increasing the dose of aclarubicin in CAG (high dose CAG, HD-CAG) regimen can safely and effectively treat relapsed or refractory acute myeloid leukemia (AML) [20]. It is unknown, however, how the therapeutic efficacy of CAG regimen for relapsed or refractory ALL compared with the other salvage regimens and whether increasing the dose of aclarubicin in CAG regimen could improve the therapeutic efficacy compared with the CAG regimen.…”
Section: Introductionmentioning
confidence: 99%
“…Наряду с высокими дозами Ара-Ц рекомендуются курсы с подкожным введением препарата в малых дозах в режиме монотерапии или комбинированной ХТ [6,[24][25][26]. Так, L. Liu и соавт.…”
Section: Discussionunclassified
“…Так, L. Liu и соавт. [25] для лечения 37 больных с рецидивами или резистентными формами ОМЛ использовали схему CAG, включавшую Ара-Ц по 10 мг/м 2 подкожно каждые 12 ч, акларубицин по 5-7 мг/м 2 внутривенно 1 раз в сутки и гранулоцитарный колониестимулирующий фактор по 200 мкг/м 2 подкожно. Все препараты вводились с 1-го по 14-й день цикла.…”
Section: Discussionunclassified
“…In AML patients who achieve complete remission following induction chemotherapy, a significant percentage of patients relapse within the first three years (2). Granulocyte colony-stimulating factor (G-SCF) priming, combined with chemotherapy, has been reported to be an effective and well-tolerated regimen in refractory or relapsed AML patients who are not eligible for intensive chemotherapy (36). In addition, immunotherapy is an active modality (7) and has had various levels of successes (8).…”
Section: Introductionmentioning
confidence: 99%